Üvegházak távoli felügyelete - Matijevics, István (Jelenkori Társadalmi és Gazdasági Folyamatok, 2010)
This paper describes the implementation and configuration of the remote control and wireless sensor network using the Sun SPOT platform. As it is well known, greenhouses have a very extensive surface where the climate conditions can vary at the different points. In the last years, remote control and WSNs are becoming an important solution to this problem. Additional advantages of remote control are the possibility of control and monitoring these applications from remote places and having a system that can provide large amounts of data about those applications for longer periods of time. This large amount of data availability usually allows for new discoveries and further improvements.